Non-dioxin-like polychlorinated biphenyls (NDL-PCBs) in eel, trout, and barbel from the River Roya, Northern Italy. (15th May 2015) - Squadrone, S.; Mignone, W.; Abete, M.C.; Favaro, L.; Scanzio, T.; Foglini, C.; Vivaldi, B.; Prearo, M.
Highlights: NDL-PCB levels in fish from the River Roya were complain to EU Regulation. The distribution of congeners did not show any significant variations between fish species. There was a higher proportion of 153, 138 and 180 congeners, according to their high resistance to metabolic degradation. Abstract: Non-dioxin-like polychlorinated biphenyls (NDL-PCBs) contribute to the dietary intake of total PCBs. They are consumed via ingestion of contaminated fish and fishery products. Thus, it is important to quantify their levels in aquatic organisms in order to evaluate the risks associated with fish consumption by humans. In 2013, an advisory against consumption of fish from the River Roya (IT) was disseminated after NDL PCBs were found to exceed maximum levels set by EU Regulations. We investigated the presence of NDL PCBs in eel, trout and barbel from the River Roya. We found concentrations in the range of 9.2–27.6 ng g − 1 ww in barbel, 9.2–97.0 ng g −1 ww in trout and 9.0–239.5 ng g −1 ww in eel. The distribution of congeners among different species did not show significant variations and was characterized by a higher proportion of 153, 138 and 180 congeners, according to their high resistance to metabolic degradation.